Pemahaman Konsep Materi Metabolisme pada Siswa Kelas XII MIPA - Anzani, Fitri; Mardiyyaningsih, Asriah Nurdini; Candramila, Wolly (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Good, broad, and in-depth mastery of concepts is very necessary to avoid misconceptions which may influence mastery of concepts in subsequent interconnected material. Low understanding of concepts can be seen from the low material completeness scores as found in class XII MIPA MA Negeri 1 Pontianak in two consecutive academic years, especially in the Metabolism material. This research aims to describe students' understanding of concepts and find out concepts that are difficult for class XII MIPA MA Negeri 1 Pontianak students to understand in Metabolism material. This research uses a survey method with a quantitative descriptive approach. The sample was taken randomly, namely one of three classes XII MIPA at MA Negeri 1 Pontianak in the 2023/2024 academic year, totaling 31 individuals. A two-tier diagnostic test instrument in the form of multiple choices is used to test understanding of the concepts of enzymes, catabolism and anabolism which consists of 20 questions. A combination of first and second level answers is used to differentiate between students who understand the concept, misconception type 1, misconception type 2, and do not understand the concept. The test results show that students' understanding of Metabolism material is in the very low category at 74.19%, in the low category 19.35%, in the medium category 6.45%, and in the high and very high categories 0%. The metabolism material that is most difficult for students to understand is the catabolism sub-material with a percentage of not understanding the concept of 50.69%, misconception type 2 41.93%. However, the percentage of misconceptions type 2 and not understanding concepts in the catabolism sub-material is also high at 50.00% and 33.33% respectively. Likewise, in the enzyme sub-material, the percentage of misconception type 2 was 38.24% and 37.32% did not understand the concept.